Understanding literacy development a global view - McKeough, Anne (L. Erlbaum Associates, 2006)
"At a time when education is burdened by increasing economic pressure to do more with less, it is imperative that educators and decision makers at all levels have access to current, broad-ranging, and in-depth information and evidence to inform their choices. This volume, compiling critical research on a wide spectrum of literacy concerns, is an invaluable tool for scholars, teacher educators, professionals, and graduate students in the fields of literary education, early childhood education, educational psychology, educational policy, and related areas."--Book jacket.